IMPLEMENTASI DAN IMPLIKASI UU NO. 23 TAHUN 2011 TERHADAP PENGELOLAAN ZAKAT (Studi Pengelolaan Zakat Di BAZNAS Kabupaten Rejang Lebong) - Hafizano, Hafizano (UIN Fatmawati Sukarno Bengkulu, 2018)
The study aims to answer the question of how the role of BAZNAS Rejang Lebong Regency in implementing Law no. 23 of 2011 on the collection and distribution of zakat. How is the impact of the implementation of Law no. 23 Year 2011 on the management of zakat ?. And What are the constraints and strategies facing BAZNAS Rejang Lebong Regency in implement- ing the Act on the management of zakat ?. This research is a qualitative research using research approach, phenomenological, sociological and historical approach. This research uses field research type (field research), that is a research conducted inten- sive, detailed and deeply to a certain object. Data Collection Techniques This research is primary data and secondary data. In accordance with the characteristics of empirical legal research using secondary data as the initial data obtained from primary and secondary legal materials, then continued with primary data or field data obtained from documents, interviews and observations. The results showed; First, that the implementation of Law no. 23 Year 2011 in the management of zakat has run optimally in accordance with the mandate of the Act. Second, the implications of the implementation of the Law on the management of zakat has given a positive effect. Proven with ZIS funds received in 2012-2016 there is an increase and ZIS funds have been distributed to mustahiq. Thirdly, the obstacles faced by BAZNAS Rejang Lebong Regency in implementing the Zakat Law are: (a) The absence of sanction for muzakki not paying zakat, (b) Some people consider BAZNAS Kab. Rejang Lebong is the same as a community organization, whereas BAZNAS is the official government institution regulated by law. (C) There are still many people who are less concerned about the obligations of zakat and the lack of zakat awareness through an institution. (D) Most Dhuafa ‘consider BAZNAS’s assistance as consumptive. The Strategy pursued by BAZNAS in the management of zakat are: First, BAZNAS cooperates with Rejang Lebong Regency Government so that it is issued Lo- cal Regulation and Regulation of Bupati. Secondly, BAZNAS’s effort in managing ZIS is by way of socialization and cooperation with religious leaders and community leaders. Thirdly, Mustahiq who is reluctant to return t he productive zakat funds then for the fund the continuation is not given anymore